A leafy surprise: Case report of male breast malignant phyllodes. (November 2021) - Khalid, Ibtissam Bin; Parvaiz, Muhammad Asad; Sarwar, Albash; Shaikh, Omair Shahid; Javed, Nida; Fatima, Arooj
Abstract: Introduction and importance: Phyllodes tumor is a biphasic fibroepithelial tumor which accounts for less than 1% of all breast neoplasms. We aim to raise awareness among clinicians that a male breast lump may be indicative of underlying sinister pathology and therefore, should be investigated thoroughly. Case presentation: A 62 year old male presented in clinic with right beast lump for the last 6 weeks. A preoperative diagnosis of spindle cell tumor was made on core needle biopsy. Neoadjuvant chemotherapy was administered in order to downsize the tumor as it was inseparable from underlying muscle. A post-operative diagnosis of malignant phyllodes was made following mastectomy. As the tumor was 1 mm from the deep margin, adjuvant radiotherapy was administered. Clinical discussion: Differential diagnoses of malignant phyllodes include metaplastic carcinomas metastatic/primary sarcomas and fibroadenomas. Metaplastic carcinomas are morphologically heterogeneous and include adenosquamous carcinoma, squamous cell carcinoma and spindle cell carcinoma. In some malignant phyllodes, extensive stromal proliferation can make detection of epithelial component very difficult. This highlights the limitation of core biopsy in establishing an accurate preoperative diagnosis. The standard treatment for phyllodes treatment is surgical resection with margins of 1 cm or more. Adjuvant radiotherapy is used in cases with threatened margins. Conclusion: Malignant phyllodes tumor of breast can exist in men, and its accurate pre-operative diagnosis is difficult given the limitations of core biopsy. This case report draws attention to the challenges associated with the diagnosis of this rare condition and highlights the role of different treatment modalities in its management. Highlights: Only a handful cases of male breast malignant phyllodes have been reported Male breast lump may be indicative of underlying sinister pathology and therefore, should be investigated thoroughly. Core Biopsy is an important diagnostic tool but has limitations in diagnosis of malignant phyllodes Treatment options include surgical resection and adjuvant radiotherapy in cases with threatened margins Neoadjuvant chemotherapy may be utilized in selective patients